Poly (ADP-ribose) polymerase 1 and Parkinson's disease: A study in post-mortem human brain. (March 2021) - Salemi, Michele; Mazzetti, Samanta; De Leonardis, Mara; Giampietro, Federica; Medici, Valentina; Poloni, Tino Emanuele; Cannarella, Rossella; Giaccone, Giorgio; Pezzoli, Gianni; Cappelletti, Graziella; Ferri, Raffaele
Abstract: Poly (ADP-ribose) polymerase 1 (PARP1) is crucial in both maintenance of genome integrity and cell death. PARP1 activation has been very recently linked to Parkinson's disease (PD) and its role in inducing the pathologic accumulation of α-Synuclein demonstrated in a PD mouse model. The objective of this study was to investigate the presence and localization of PARP1 in PD brain. PARP1 localization was assessed by immunostaining and confocal microscopy in post-mortem human brains obtained from PD patients (Braak stage VI) compared to controls. PARP1 positive nuclei in substantia nigra, mainly in dopaminergic neurons but also in astrocytes and oligodendrocytes, were decreased in PD. The same alteration was observed in several areas that are affected in PD pathology, namely the dorsal motor nucleus of vagus, frontal and cingulate cortex, whereas no changes in PARP1 staining were detectable in the inferior olivary nucleus that is unaffected in PD. In addition, PARP1 co-localizes with α-Synuclein that is accumulated in the cytoplasm and in Lewy bodies of PD tissue sections. Our data reveal previously unknown changes of PARP1 localization in the brain of PD patients, in both neurons and glia, supporting its widespread involvement in this pathology and its potential use as a therapeutic target. Highlights: PARP-1 analysis reveals changes in Parkinson's disease patients. PARP-1 is linked to α-Synuclein pathology in human brain. Changes in PARP-1 suggest novel hint for therapy in neurodegeneration.